2018
DOI: 10.1038/s41598-018-30183-5
|View full text |Cite
|
Sign up to set email alerts
|

Tactile learning transfer from the hand to the face but not to the forearm implies a special hand-face relationship

Abstract: In the primary somatosensory cortex, large-scale cortical and perceptual changes have been demonstrated following input deprivation. Recently, we found that the cortical and perceptual changes induced by repetitive somatosensory stimulation (RSS) at a finger transfer to the face. However, whether such cross-border changes are specific to the face remains elusive. Here, we investigated whether RSS-induced acuity changes at the finger can also transfer to the forearm, which is the body part represented on the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…This has already been indicated by studies on M1 neurodegeneration where disease spread markedly differs depending on which body part is first affected [38]. Other than previously described for the primary somatosensory cortex of younger adults [39], [40], our findings indicate that plasticity and disease mechanisms in M1 may not transfer to other body parts.…”
Section: Discussionsupporting
confidence: 72%
“…This has already been indicated by studies on M1 neurodegeneration where disease spread markedly differs depending on which body part is first affected [38]. Other than previously described for the primary somatosensory cortex of younger adults [39], [40], our findings indicate that plasticity and disease mechanisms in M1 may not transfer to other body parts.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, in physiological state, a study of fMRI showed speci c correlation between LI4 and orofacial muscles, activating a wide range of overlapping and adjacent brain regions [44]. Furthermore, somatosensory stimulation can induce plasticity changes across hand and face representation, both in primary sensory cortex [45,46] and motor cortex [47]. These ndings provide evidences for explaining the relation between hand and face.…”
Section: Discussionmentioning
confidence: 99%
“…Three hours of repetitive somatosensory stimulation at the right index fingertip produced significant shifts in dipole location in the sensory cortex for both the index fingertip and the upper‐lip and improved 2‐point discrimination at the index fingertip and at the non‐stimulated upper lip (Muret et al, 2014, 2016). This finger‐to‐lip transfer appears to be specific to the face, as a subsequent study showed that two‐point discrimination was not improved on the forearm (Muret & Dinse, 2018).…”
Section: Introductionmentioning
confidence: 91%